Effects of National Institutions on Corporate Brand Ability Associations During the Pandemic - Nele Jacobs; Bernhard Swoboda (Management International Review, 2023)
During the COVID-19 pandemic, consumer behavior and brand preferences changed. However, surprisingly little is known about how or why corporate brand associations differ and change across countries during such black swan events, especially for multinationals with a specific expertise and ability, for example, to offer vaccines. The authors use institutional theory to fill this gap. They contribute to international business research by analyzing the roles of national institutions in consumers' corporate brand ability associations (CBAA) in 20 countries over time. They find generally different roles of regulative, normative, and cultural-cognitive institutions in consumers' CBAA. Moreover, those roles changed and varied for Pfizer, as a multinational corporation that offered the first vaccine in Western countries, and its competitors before and during the pandemic. Institutional theory strongly complements signaling theory in cross-national studies on CBAA. This study shows, for the first time, which institutions drive CBAA cross-nationally and why the role of each institution changes during a black swan event, such as COVID-19. It has direct implications for managers interested in cross-national consumer responses.
Keywords: 330; National institutions; Corporate brand; Ability associations; COVID-19; Cross-national research